Pilot observations for MALT-45: a Galactic plane survey at 7 mm - Jordan, C.; Walsh, Andrew; Lowe, V.; Lo, N.; Purcell, C.; Voronkov, M.; Longmore, S. (Oxford University Press, 2013)
We introduce the Millimetre Astronomer’s Legacy Team – 45 GHz (MALT-45) Galactic plane survey and describe pilot survey results with the Australia Telescope Compact Array (ATCA).The pilot survey was conducted to test the instrumentation and observational technique ofMALT-45, before commencing the full survey. We mapped two half-square degree regions within the southern Galactic plane around the G333 giant molecular cloud, using fast mosaic mapping. Using the new Compact Array Broad-band Backend on the ATCA, we were able to observe two 2048MHzspectral windows, centred on frequencies 43.2 and 48.2 GHz. Although only a coarse spectral resolution of around 7 km s-1 was available to us, we detect widespread, extended emission in the CS (1–0) ground state transition. We also detect eight Class I CH3OH masers at 44 GHz and three SiO masers in vibrationally excited (1–0) transitions. We also detect the H53a radio recombination line, non-vibrationally excited SiO (1–0) and emission in the CH3OH 11–00 A+ line.